Causal factors influencing quality of treatment and survival in Wilms Tumor: A retrospective investigation - Syed Ibrahim Bukhari; Zahra Saeed Ahmed; Javeria Saeed; Kiran Hilal; Zehra Fadoo; Naureen Mushtaq; Bilal Mazhar Qureshi; Sadaf Altaf (Pediatric Hematology Oncology Journal, 2023)
Background: Wilms Tumor (WT) is a highly curable cancer if treatment is appropriate and timely. The outcomes and prognostic factors in a large low- and middle-income country (LMIC) tertiary center were assessed. Materials and methods: Retrospective review of data of all patients, 0–15 years diagnosed between 2010 and 2020 with WT. Kaplan Meier curves were used for survival analysis, and the chi-square test was used for multivariate analysis. Results: Of the 40 patients enrolled (median age: 38 months) in the cohort, 10 had metastatic disease. The most common site of metastasis was lungs (6/10). Nine (22.5%) abandoned treatment. Large tumor (>500 ml) volume was found in half the patients at diagnosis. The majority of patients were treated per the SIOP approach. Out of 34 who went for surgery, 31 received neoadjuvant chemotherapy with tumor shrinkage to less than 500 ml in 26/31 (80%). Maximum tumor shrinkage was observed in the SIOP low-risk group (p < 0.05). Accurate lymph node sampling (≥7) was performed in 7/34 (20%). The SIOP tumor stages were I (n = 14), II (n = 3), III (n = 6), IV (n = 9), and V (n = 5). One of the 31 treated patients vis-à-vis 8 of the patients who abandoned treatment died (p < 0.05). The overall survival and relapse-free survival of all 40 patients were 77.5% and 87.5%, respectively, with a median follow-up period of 25 months. Conclusion: A higher risk histology and abandonment were identified as adverse prognostic factors. The survival could potentially be improved by early referral and initiation of standardized treatment along with adequate lymph node sampling.